The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s10900-012-9589-1
|View full text |Cite
|
Sign up to set email alerts
|

HPV Infection Awareness and Self-Reported HPV Vaccination Coverage in Female Adolescent Students in Two German Cities

Abstract: Low levels of human papillomavirus (HPV) awareness and knowledge have been observed in the few studies conducted among school-going adolescents. Such data are lacking in Germany. To assess awareness of HPV and of vaccination status among girls attending grades 8-13 in Bremen and Bremerhaven, two German cities. Participants completed a questionnaire in school including questions on demographic characteristics, about HPV awareness and on vaccination status. We analysed the relationship between awareness of HPV, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
8
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
(27 reference statements)
3
8
0
1
Order By: Relevance
“…With regard to sexual behaviour, virgins were less likely than nonvirgins to have heard of HPV, which is similar to previous findings (Blodt et al, 2012;Samkange-Zeeb et al, 2012;Donadiki et al, 2013). Among nonvirgins, women who were less sexually experienced in terms of late sexual debut or (in Denmark) a low number of sexual partners were less likely to have heard of HPV.…”
Section: Discussionsupporting
confidence: 87%
“…With regard to sexual behaviour, virgins were less likely than nonvirgins to have heard of HPV, which is similar to previous findings (Blodt et al, 2012;Samkange-Zeeb et al, 2012;Donadiki et al, 2013). Among nonvirgins, women who were less sexually experienced in terms of late sexual debut or (in Denmark) a low number of sexual partners were less likely to have heard of HPV.…”
Section: Discussionsupporting
confidence: 87%
“…6 Previously conducted coverage studies from Germany, which were mainly based on survey data, have shown heterogeneous results, depending on the considered age group, region, and study population. [3][4][5]7 Direct comparability of our results with those studies is hampered by different aspects. First of all, an estimation of the vaccination coverage rather than the vaccine uptake was not possible in the context of the present study due to the limited study period (only the year 2008), for which the data was available.…”
mentioning
confidence: 86%
“…2 Based on data from several surveys, HPV vaccination coverage in Germany with at least one vaccine dose ranged from 12% in females aged 12-20 y to 67% in females aged 18-20 y. [3][4][5] In one of these studies, the proportion of girls not knowing, whether they had received the vaccination was shown to be 57%, 5 suggesting that recall bias might considerably affect the validity of self-reported data in this context. 6 Vaccination record review (n = 161) including females aged 14-19 y showed an HPV vaccination coverage with all three recommended doses of 41% in the federal state of Berlin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mädchen scheinen überwiegend über den Zusammenhang zwischen HPV und Krebs und über die Möglichkeit der Impfung informiert zu sein; allerdings ist der Mehrheit der Befragten die hohe Wahrscheinlichkeit für eine Infektion nicht bewusst [8,27,28]. Immerhin fast 20 % der im Auftrag der BZgA im Jahr 2012 befragten jungen Frauen kannten die HPV-Impfung nicht oder hatten keine Meinung zur Bedeutung der Impfung [5].…”
Section: Wissen Und Einstellungunclassified